Science Teachers' view on Sustainable Development in COVID-19 Pandemic Process - Hakan Türkmen (Universitas Pendidikan Indonesia, 2022)
This study examines what science teachers think about Sustainable Development and its' Goals, how they integrate SDGs into their science lessons, and how the covid-19 pandemic affects their thoughts about Sustainable Development. The study group was selected by convenience sampling from 51 middle schools in the central district of one of the big cities. The questionnaire, including five open-ended questions, was prepared and checked by two experts. After their feedback, it was re-corrected and then applied to the participants. It was conducted using the